Cloning and expression of Bacillus subtilis genes in Streptomyces sp. - Salman, E. D. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A local isolate Bacillus subtilis was used, which producing thennophilic complex enzyme having similar activity of endogluganase enzyme ( Endo-l,4-B-Dglucanase ). Partially digested chromosomal DNA of Bacillus subtilis by Eco Rl restriction enzyme randomly cloned into Eco Rl pSU10l shuttle vector. The resulted hybrid plasmid was transformed into protoplast of Streptomyces sp. SH-H. The result revealed that cellulose genes, which expressed into transfonned cells are located on chromosomal DNA fragment having size 4.5Â·5 kb in size.